Dasiglucagon Effects on QTc in Healthy Volunteers: A Randomized, Placebo-Controlled, Dose-Escalation, Double-Blind Study - Ramin Tehranchi, MD, PhD, MBA; Jonas Pettersson, MD, PhD; Anita E. Melgaard, MSc; Friedeborg Seitz, MD; Anders Valeur, PhD; Stine Just Maarbjerg, PhD (Elsevier, 2022)
ABSTRACT: Background: Dasiglucagon is a novel glucagon analog that is stable in aqueous formulation and approved for use in severe hypoglycemia. Concentration-QTc analyses are critical for assessing risk of drug-induced QTc prolongation and potential for fatal cardiac arrhythmias such as torsades de pointes. Objective: The aim of this study was to determine whether dasiglucagon treatment resulted in any clinically relevant effect on cardiac repolarization in healthy volunteers. Methods: This double-blind, placebo-controlled, dose-escalation Phase I trial was conducted at a single center in Germany between November 2018 and June 2019. Sixty healthy volunteers aged 18 to 45 years were randomized within dose cohorts to receive intravenous dasiglucagon, intravenous placebo, or subcutaneous dasiglucagon. In the intravenous administration cohorts, doses ranged from 0.03 mg to 1.5 mg. The subcutaneous administration cohort received the approved 0.6 mg dose. In the intravenous administration cohorts, serial electrocardiograms were extracted from continuous Holter monitors at prespecified time points beginning the day before dosing and through 24 hours postdose. Heart rate, PR interval, and QRS duration were evaluated. Concentration-QT analyses corrected by Fridericia's formula (QTcF) were performed using both a linear mixed-effects and an estimated maximum effect (Emax) model. Results: At the doses studied, dasiglucagon did not have any clinically relevant effect on heart rate, PR interval, or QRS duration. A minor prolongation of the QTcF interval was observed without any clear dose or concentration dependency. Both the linear and Emax models predicted mean and 90% CIs of placebo-corrected change in QTcF remained below 10 ms (the threshold of regulatory concern), although the linear model did not fit the data well at low dasiglucagon plasma concentrations. In the Emax model, the Emax of dasiglucagon was 3.6 ms (90% CI, 1.23-5.95 ms), and the amount to produce half the effect of Emax) was 426.0 pmol/L (90% CI, −48.8 to 900.71 pmol/L). The treatment effect-specific intercept was −0.44 ms (90% CI, −2.37 to 1.49 ms). The most frequently observed treatment-emergent adverse events reported in the trial were gastrointestinal disorders such as nausea and vomiting. Conclusions: Dasiglucagon does not cause clinically relevant QTc prolongation in concentrations up to ≈30,000 pmol/L, a level 5-fold higher than the highest observed plasma concentrations in clinical trials investigating use of the approved 0.6 mg SC dose. ClinicalTrials.gov Identifier: NCT03735225; EudraCT identifier: 2018-002025-32. (Curr Ther Res Clin Exp. 2022; 83:XXX-XXX)